2020
DOI: 10.3390/agronomy10091369
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Management of PSII-Inhibitor-Resistant Chenopodium album L. in Atlantic Canadian Potato Production

Abstract: Potato producers in the Atlantic Canadian provinces of New Brunswick (NB) and Prince Edward Island (PE) rely on the photosystem II-inhibiting herbicide metribuzin for weed management. Recently, potato producers in the region have reported unacceptable common lambsquarters control following an application of metribuzin. Tissue and seed samples were collected from escaped common lambsquarters populations from across the potato producing regions of NB and PE and screened for the Ser264Gly mutation in psbA. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Resistance is defined as the inherited ability of a plant/weed to survive and reproduce following exposure to a herbicide dose that used to be lethal to the same weed species. For example, Senecio vulgaris (L.) was the first weed that showed resistance to triazine herbicides but to date, 511 unique cases of herbicide-resistant weed species have been reported globally [4,5]. These cases have increased by 14% (233 to 266) in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance is defined as the inherited ability of a plant/weed to survive and reproduce following exposure to a herbicide dose that used to be lethal to the same weed species. For example, Senecio vulgaris (L.) was the first weed that showed resistance to triazine herbicides but to date, 511 unique cases of herbicide-resistant weed species have been reported globally [4,5]. These cases have increased by 14% (233 to 266) in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Common lambsquarters has historically been controlled in potato with metribuzin and linuron. However, widespread resistance of common lambsquarters to the PSII-inhibiting herbicide metribuzin now occurs across the Atlantic Canada potato-growing region (McKenzie-Gopsill et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pandian et al [5] reported on the first case of TS resistance to ALS inhibitors in a Poly-gonum convolvulus population from KS, USA. McKenzie-Gopsill et al [6] described TS resistance of Chenopodium album to metribuzin, a photosystem II-inhibiting herbicide. The authors also demonstrated alternative herbicide application for weed control in the Atlantic Canadian potato agro-system to overcome the development of herbicide resistance.…”
mentioning
confidence: 99%